Pengaruh Pendampingan Orang Tua Terhadap Prestasi Siswa di SD Patra Dharma 3 Balikpapan - Kharismatika, Anzilnaa; Yusuf, Iskandar (Sekolah Tinggi Ilmu Tarbiyah Al Mubarok Bandar Mataram, 2025)
Education is a planned process to optimally develop the potential of students, with the family serving as the primary and main educational environment responsible for supporting a child's success. Parental guidance is defined as the activity of parents accompanying or assisting their children, especially in the learning process, reflecting their attention and care for the child's academic development. Student learning achievement is the result achieved by students in learning activities, measured through academic scores or certain achievements, which serves as an indicator of educational success. This study aims to analyze the influence of parental guidance on student achievement at SD Patra Dharma 3 Balikpapan. This research employed a mixed-methods approach, combining quantitative methods to determine statistical relationships and qualitative methods to deepen the understanding of the phenomenon. A total of 36 sixth-grade students (6A and 6B) at SD Patra Dharma 3 Balikpapan served as research respondents. Data were collected through questionnaires to measure the level of parental guidance and student learning achievement, as well as interviews and observations to gather in-depth information. Quantitative data were analyzed using regression analysis, while qualitative data were analyzed using content analysis techniques. The research results indicate a significant influence between parental guidance and student learning achievement, but the direction of this relationship is negative. This means that an increase in the intensity of parental guidance does not always correlate with an increase in academic achievement. These findings highlight the importance of internal factors such as self-motivation, learning independence, and values instilled within the family as primary determinants of academic success. Therefore, parental guidance strategies need to be adapted to the individual characteristics and needs of students, and oriented towards strengthening motivation and independence in learning. Academic success is not solely determined by the intensity of parental guidance, but also by strong motivation and self-reliance values instilled early in the family.